Big data of open source ecosystem for intelligent software development - Yang ZHANG; Tao WANG; Gang YIN; Yue YU; Jingquan HUANG (大数据)
The open source software development process contains a lot of valuable data, which is huge in scale, fragmented, and rapidly expanding. Aimming to the characteristics, the big data structure of open source ecosystem of software engineering was studied, and a self-growing collection and processing framework and a convergence and sharing environment was proposed. The related research on the development of intelligent software based on open source big data of software engineering, and typical applications based on analysis and mining of open source big data of software engineering were expounded, and relevant guidance for the research and application of big data of open source ecosystem for intelligent software development was provided.